PENGALAMAN BULLYING DI SEKOLAH DAN HUBUNGANNYA DENGAN FAKTOR POLA ASUH DALAM KELUARGA - Cristanty, Siska; Siswoyo, Edy (Jurnal Insani, 2020)
With the background of the many cases of bullying in the school environment, this study tries to answer the question: How is the bullying experience of students? What is the parenting style of these students? Is there any effect of parenting on students' bullying behavior? Are there other factors that influence students' bullying behavior? Data collection was carried out on schools and all students of SMK Negeri 17 Jakarta through the distribution of digital questionnaires from March to March. June 2020. The data were analyzed using STATA Version 11. The results of the study concluded that 1) Bullying is a social problem and the experience of bullying behavior in SMK Negeri 17 Jakarta students was found to be 96 students from a total of 385 respondents who responded to the questionnaire. 2) The parenting pattern of the students of SMK Negeri 17 Jakarta is dominated by authoritative parenting style, and when it is associated with bullying behavior, the neglectful and authoritarian parenting style has the greatest influence on bullying behavior. 3) Other factors that also influence the bullying behavior of SMK Negeri 17 Jakarta students besides parenting are internal factors (gender, height and weight, experience of being bullied), family factors (marital status and parental occupation, number of pocket money), environmental factors (home, school, association), and the media.